Decarbonizing Germany's heating sector - Ralf Dickel (The Oxford Institute for Energy Studies, 2024)
By its Climate Protection Act Germany is committed to net zero GHG emissions by 2045, implying zero emissions from space heating, a major part of final energy consumption. The present political discussion reflected in recent legislation is dominated by use of heat pumps and renewable power. This approach risks to fail due to too slow renewable roll out, bottlenecks in power infrastructure and lack of storage solutions to cover the strong seasonality of heating demand, from today's 9.5 million gas heated and 6 million oil heated buildings (ca 80% of overall buildings). Replacing oil heating of 5 million buildings on the countryside by heat pumps has little alternative. This paper illustrates that including district heating and switching from natural gas to green and blue hydrogen for about 5 million buildings each in urban areas, offers a realistic way to a zero CO2 heating sector by 2045. It suggests early actions needed to foster each of the three avenues and above all a paradigm change accepting that renewable energy supply and heat pumps have to be complemented by fossil fuels with CCS to achieve reliable and CO2 free heating by 2045.
Keywords: 330; district-heating; early actions; German Climate Protection Act; heat-pumps; switch to hydrogen; zero CO2 emission heating